L’intégration du théâtre forum et son prolongement audiovisuel dans le processus communicationnel interne de sensibilisation au développement durable et d’appropriation de cette notion chez les salariés d’une organisation - Franck Debos; Natacha Cyrulnik; Francine Boillot; Céline Lacroix (Communication)
Sustainable development is a central dimension in the management and communications of any organization. This article examines how employees appropriate this concept of sustainable development and how they build their commitment to this end. The results of our research action project involving a sample of employees from L’Archet University Hospital (CHU) in Nice and from the Agora Energy network suggest that even though our respondents did not “naturally” refer to the theater forum as an awareness-raising tool about sustainable development, after first experiencing this mode of representation, it did facilitate the appropriation of concepts such as sustainable development.